Persistent income inequality in Sub-Saharan Africa: The role of institution index and effective VAT - Tewa Papy Voto; Nicholas Ngepah (Economies, 2025)
As countries worldwide endeavor to fulfill the United Nations Sustainable Development Goal (SDG) 10, which emphasizes reducing inequality, there is a growing imperative to utilize tax policy and institutions to accomplish this objective. Hence, this study is inspired by this rationale. The aim of this study is to assess the relationship between effective VAT (calculated as total VAT revenues divided by final consumption, which reflects the economic incidence of the tax rather than its legal definition), institution index, and income inequality. To achieve this objective, this study uses the system generalized method of moments (SGMM) for 35 Sub Saharan Africa countries from 1995 to 2021. The results show that effective VAT increases income inequality in both the short and long run. However, the effect of the long run is greater than that of the short run. Furthermore, the results reveal that institutional quality reinforced the positive effect of effective value added tax on income inequality in both the short and long run, with the long run being more pronounced than the short run. This suggests that effective VAT policies and institutional quality applied in this study augment income inequality. Additionally, it is also noticed that ethnic fragmentation impedes effective VAT to lower income disparity in the short and long run in SSA. Hence, a relevant policy to strengthen the tax system and improve institutional quality should be given priority in SSA.
Keywords: H20; O11; O15; 330; effective VAT; income inequality; institutional quality; SGMM